THE INFLUENCE OF FORCED AGED ENGINE OILS ON THE TRIBOLOGICAL CONDITION OF THE MODEL TRIBOUNIT - Кубіч, Вадим; Чернета, Олег; Мимоход, Дмитро (Problems of Friction and Wear, 2022)
The results of tribotechnical tests of lubricating formations, which were formed under the conditions of supply of motor oils AZMOL 15W40 CI-4/SL, EVO 5W40 SN/CF and its absence on the friction surfaces of the elements of the model tribojoint "moving disc - fixed pad" for the tribosystem of materials "40X-AO20-1", are given. At the same time, the motor oil samples were previously forcibly subjected to interaction with the crankcase gases of the VAZ-21011 engine with different intensity of breakthrough through the CPG gap of the internal combustion engine. On the basis of the established regularities of the change in the dynamic coefficient of friction under step loading and the relative temperature during the tests, it was established that in the absence of lubrication of the friction zones, mineral motor oil with changed performance indicators worsens the tribological condition of the studied system of materials, while synthetic oil, on the contrary, improves it. It was determined that, according to the general cycle of tests, the wear intensity of the AO20-1 alloy is increased by 1.26 and 1.33 (relative to the normative value of p=12 kgf/cm2) times when the intensity of gas breakthrough is increased by the pressure parameter per compression stroke, with mineral oil it increases by 1.89 and 3.2 times, respectively. At the same time, with synthetic oil, the wear intensity is reduced by 1.15 times. In general, the wear intensity of the AO20-1 alloy proposed for use when using synthetic oil forcibly aged by crankcase gases with the critical intensity of gas breakthrough is 1.7 times less than for mineral oil. However, at p = 9.5 kgf/cm2, the given wear intensities are relatively equal. The obtained data are explained by the complexity of the flow of chemical-mechanical processes of adhesive interaction between the components of motor oils and the chemical elements of the AO20-1 antifriction alloy. The obtained results are significant for the development of recommendations for ensuring the operational reliability of gasoline internal combustion engines at the stages of resource loss before overhaul.